The relationship of inertias between two representations of linear subspaces. (1st November 2020) - Ocaña, Eladio; Flores-Luyo, Luis
Abstract : This work gives complete expressions of inertia of matrices involved in a linear subspace of R n × R n when they are presented in two different ways, specifically, as image and as well as kernel of linear maps.